The Monk by M. G. Lewis: Revolution, Religion and the Female Body - Łowczanin, Agnieszka (Text Matters: A Journal of Literature, Theory and Culture, 2016)
This paper reads The Monk by M. G. Lewis in the context of the literary and visual responses to the French Revolution, suggesting that its digestion of the horrors across the Channel is exhibited especially in its depictions of women. Lewis plays with public and domestic representations of femininity, steeped in social expectation and a rich cultural and religious imaginary. The novel’s ambivalence in the representation of femininity draws on the one hand on Catholic symbolism, especially its depictions of the Madonna and the virgin saints, and on the other, on the way the revolutionaries used the body of the queen, Marie Antoinette, to portray the corruption of the royal family. The Monk fictionalizes the ways in which the female body was exposed, both by the Church and by the Revolution, and appropriated to become a highly politicized entity, a tool in ideological argumentation.